2000
DOI: 10.1074/jbc.275.17.12374
|View full text |Cite
|
Sign up to set email alerts
|

TFIIA Has Activator-dependent and Core Promoter Functions in Vivo

Abstract: The physiological role of TFIIA was investigated by analyzing transcription in a yeast strain that contains a TATA-binding protein (TBP) mutant (N2-1) defective for interacting with TFIIA. In cells containing N2-1, transcription from a set of artificial his3 promoters dependent on different activators is generally reduced by a similar extent, indicating that TFIIA function is largely nonselective for activators. In addition, TATA element utilization, a core promoter function, is altered at his3 promoters depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 68 publications
(69 reference statements)
1
21
1
Order By: Relevance
“…When the amount of RNA initiating from ϩ1 (which is driven by the noncanonical element, T C ) and ϩ13 (driven by TATA) start sites were compared, the N2-1 strain showed a preferential increase in transcription initiating from ϩ13, even when the overall level of transcription was low (33). This is in stark contrast to the utilization of the HIS3 promoter elements occurring in wild type cells, which shows similar levels of output (22).…”
Section: Mechanistic Differences Between Canonical and Noncanonical Econtrasting
confidence: 45%
See 2 more Smart Citations
“…When the amount of RNA initiating from ϩ1 (which is driven by the noncanonical element, T C ) and ϩ13 (driven by TATA) start sites were compared, the N2-1 strain showed a preferential increase in transcription initiating from ϩ13, even when the overall level of transcription was low (33). This is in stark contrast to the utilization of the HIS3 promoter elements occurring in wild type cells, which shows similar levels of output (22).…”
Section: Mechanistic Differences Between Canonical and Noncanonical Econtrasting
confidence: 45%
“…Depend on TFIIA Activity-Recent work characterizing a TBP allele defective for interaction with TFIIA (the N2-1 derivative of TBP) has shown that the TFIIA-TBP interaction is important for HIS3 core element utilization (33). When the amount of RNA initiating from ϩ1 (which is driven by the noncanonical element, T C ) and ϩ13 (driven by TATA) start sites were compared, the N2-1 strain showed a preferential increase in transcription initiating from ϩ13, even when the overall level of transcription was low (33).…”
Section: Mechanistic Differences Between Canonical and Noncanonical Ementioning
confidence: 99%
See 1 more Smart Citation
“…Several approaches have been taken to determine which genes require TFIIA for expression in vivo. These include TFIIA subunit depletion, mutation of TFIIA subunits to impair interaction with TBP, or mutation of TBP to inhibit interaction with TFIIA (Kang et al 1995;Ozer et al 1998a;Liu et al 1999;Stargell et al 2000). These studies generally agree that TFIIA is important for transcription of a specific subset of genes, although there is not yet agreement on the exact subset of genes requiring TFIIA for normal expression.…”
mentioning
confidence: 70%
“…The general transcription factor TFIIA accelerates and stabilizes binding of TBP to TATA boxes (19 -21). It also functions as a co-activator for some transcriptional activators (22)(23)(24)(25)(26). TFIIA further functions as an antagonist of NC2 (also called Dr1/DRAP) (27,28).…”
mentioning
confidence: 99%